2014
DOI: 10.1007/s00339-014-8683-x
|View full text |Cite
|
Sign up to set email alerts
|

Retroreflection of light from nanoporous InP: correlation with high absorption

Abstract: Pronounced retroreflection behavior is reported for a fishnet nanoporous strongly absorbing semiconductor material. Retroreflection appears along with diffusive specular reflection for all angles of incidence for light wavelength corresponding to interband optical transitions, where absorption coefficient is of the order of 10 5 cm -1 (green and red light). Retroreflection is apparent by the naked eye with daylight illumination and exhibits no selectivity with respect to wavelength and polarization of incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Due to these regularities it was possible to observe the phenomenon of anomalous retroreflection in a strongly absorbing nanostructured medium in a wide frequency range [9,10] upon illumination of samples by sun radiation. The performed analysis allows one to put forward the hypothesis that at ε 1 ?ε 2 in 'tracery' nanostructures fulfilling the condition of f o =1, but made from nanostructured dissipating materials (for instance, from metals or carbon nanotubes) with a high degree of ordering, there should be no any reflected transverse waves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to these regularities it was possible to observe the phenomenon of anomalous retroreflection in a strongly absorbing nanostructured medium in a wide frequency range [9,10] upon illumination of samples by sun radiation. The performed analysis allows one to put forward the hypothesis that at ε 1 ?ε 2 in 'tracery' nanostructures fulfilling the condition of f o =1, but made from nanostructured dissipating materials (for instance, from metals or carbon nanotubes) with a high degree of ordering, there should be no any reflected transverse waves.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the observed phenomenon can be classified neither as coherent backscattering nor as Anderson localization of light, since strong absorption inhibits multiple reflection, the necessary prerequisite for coherent backscattering and Anderson localization. Pronounced correlation of the phenomenon with strong absorption has been further established experimentally [10].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In recent work, we have reported on the unusual effect of pronounced retroreflection from a nanoporous semiconductor material (InP) in the spectral range of the interband transitions with a simultaneously high refractive index (n= 3.8) and absorption coefficient (α=10 5 cm −1 ) [18]. The effect was experimentally proved to vanish for weakly absorbed light (when photon energy is less than the band gap energy, E g ) [19]. Retroreflection was observed with coherent and incoherent, monochromatic and wide-band radiation and was apparent to the naked eye with sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, III-V semiconductors have been widely used in microelectronics and optoelectronic devices [1][2][3][4][5][6][7][8] . In particularly, indium phosphide (InP), which is a well-known direct bandgap semiconductor, has attracted great attention in optoelectronic devices 1,2,7 .…”
mentioning
confidence: 99%